Generation of virtual WDS to complete cadastral information of existing systems (2017)
Information related to Water Distribution Systems (WDS) in small and intermediate cities often may be incomplete or unreliable, and data acquisition may be infeasible due to elevated time and economic costs. This lack of information can lead to inaccurate network operation and maintenance, and it can also limit the use of calibrated hydraulic models to support future designs in the system. Virtual case studies can thus be treated and used to overcome the insufficient data problems. The results are not case-specific as the obtained with benchmark networks. This paper aims to evaluate a new methodology by generating virtual networks for different cities in Colombia and then comparing resulting virtual WDS with the real systems, based on data obtained from water utilities. For both sets, network layout similarity and hydraulic factors were analysed. The results of the comparison between real and virtual networks make it possible to conclude about the applicability and limitation of this virtual generation software in small cities or DMAs in large cities, and also allows suggesting alternative solutions.